Burial, landscape and identity in early Medieval Wessex - Mees, Kate (Anglo-Saxon studies ;, 2019)
Burial evidence provides the richest record we possess for the centuries following the retreat of Roman authority. The locations and manner in which communities chose to bury their dead, within the constraints of the environmental and social milieu, reveal much about this transformational era. This book offers a pioneering exploration of the ways in which the cultural and physical environment influenced funerary traditions during the period c. AD 450-850, in the region which came to form the leading Anglo-Saxon kingdom of Wessex. This was a diverse landscape rich in ancient remains, in the form of imposing earthworks, enigmatic megaliths and vestiges of Roman occupation. Employing archaeological evidence, complemented by toponymic and documentary sources and elucidated through landscape analysis, the author argues that particular man-made and natural features were consciously selected as foci for funerary events and ritual practice, becoming integral to manifestations of identity and power in early medieval society.